Representasi kelompok lesbian, gay, biseksual, dan transgender (LGBT) dalam pemberitaan Detik.com - Rofingatun Hamidah; Tyas Retno Wulan; Arizal Mutahir (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
The Lesbian, Gay, Bisexual, and Transgender (LGBT) group is a group that is marginalized due to issues of gender and sexuality. The LGBT community is often stigmatized as immoral and deviant, considered the source of HIV/AIDS, contrary to religion, as a disease, and not by state ideology. Society's knowledge of heteronormative gender and sexuality makes the LGBT group abnormal. The media can construct or deconstruct what people believe to be true. This study intends to explain how the representation of LGBT groups in news coverage in the mass media. In particular, the news in the online media Detik.com. Detik.com was chosen because it is one of the pioneers of internet-based mass media and always occupies Indonesia's top ten most popular websites. This research used Norman Fairclough's critical discourse analysis method, focusing on social structure, class, and social relations. Norman Fairclough presents three dimensions of analysis: text analysis, discourse practice, and sociocultural practice. The study results show Detik.com reporting on LGBT issues dominates in putting LGBT groups in a corner. The LGBT group is still represented as